Efektivitas Brain Based Learning Terhadap Kemampuan Berpikir Kritis Matematis Siswa: Literatur Riview - Julia Elvina; Hasanuddin Hasanuddin (Jurnal Wahana Literasi Pendidikan, 2026)
The purpose of this article is to evaluate, through a literature review, the effectiveness of Brain-Based Learning in improving students’ critical thinking skills in mathematics. The importance of enhancing critical thinking skills in mathematics education to meet the demands of the 21st century serves as the background for this study. The approach employed is a literature review of journal articles published between 2020 and 2026, with the analysis stages consisting of identification, categorization, evaluation, and synthesis. The keywords “Brain-Based Learning,” “mathematical critical thinking,” and “berpikir kritis matematis” were used to search for articles in Sinta-indexed journal databases. Ten articles that met the eligibility criteria were identified through the selection process. The findings of this review indicate that the implementation of Brain-Based Learning generally improves students’ critical thinking skills in mathematics. Therefore, it can be concluded that Brain-Based Learning is an effective strategy for helping students enhance their critical thinking skills in mathematics.